2023
DOI: 10.1021/acs.inorgchem.3c01482
|View full text |Cite
|
Sign up to set email alerts
|

Interface Energy Alignment between Lead Halide Perovskite Single Crystals and TIPS-Pentacene

Alberto García-Fernández,
Birgit Kammlander,
Stefania Riva
et al.

Abstract: At present, there is a huge development in optoelectronic applications using lead halide perovskites. Considering that device performance is largely governed by the transport of charges across interfaces and, therefore, the interfacial electronic structure, fundamental investigations of perovskite interfaces are highly necessary. In this study, we use high-resolution soft X-ray photoelectron spectroscopy based on synchrotron radiation to explore the interfacial energetics for the molecular layer of TIPS-pentac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…To obtain reliable results, it is crucial to identify and minimize any degradation from the measurement process itself. For example, PES is extensively used to study surfaces and interfaces of lead halide perovskites 9,10 and to investigate causes for their degradation when exposed to environmental stressors like humidity or heat. 3,11,12 However, the interpretation of the results becomes more challenging if X-ray induced initial shifts in binding energy position, 13 or the formation of metallic lead (Pb 0 ) are present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain reliable results, it is crucial to identify and minimize any degradation from the measurement process itself. For example, PES is extensively used to study surfaces and interfaces of lead halide perovskites 9,10 and to investigate causes for their degradation when exposed to environmental stressors like humidity or heat. 3,11,12 However, the interpretation of the results becomes more challenging if X-ray induced initial shifts in binding energy position, 13 or the formation of metallic lead (Pb 0 ) are present.…”
Section: Introductionmentioning
confidence: 99%
“…3 To avoid these external factors, single crystal surfaces instead of thin film surfaces can be studied. We have shown that clean surfaces of perovskite single crystals can be prepared in vacuum through cleaving, 10,11,24 which enables us to study intrinsic behaviors of the material. Therefore, to take our previous study further and to gain insight into the behavior of lead halide perovskite surfaces with X-rays without the effects of grain boundaries, we decided to use perovskite single crystals in the work presented here.…”
Section: Introductionmentioning
confidence: 99%